2021
DOI: 10.1002/term.3194
|View full text |Cite
|
Sign up to set email alerts
|

Using 3D‐bioprinting scaffold loaded with adipose‐derived stem cells to burns wound healing

Abstract: Three dimensional (3D) printing has recently expanded in popularity and has become an effective approach for tissue engineering. Advances in tissue engineering have increased the effectiveness of cell-based therapies. Indeed, the ultimate goal of such treatment is the development of conditions similar to fetal wound regeneration. In this context, technology of 3D printing also allows researchers to more effectively compose multi-material and cell-laden scaffolds with less effort. In this study, we explored a s… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
39
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
9
1

Relationship

0
10

Authors

Journals

citations
Cited by 44 publications
(43 citation statements)
references
References 33 publications
(29 reference statements)
0
39
0
Order By: Relevance
“…In recent years, MSCs-derived exosomes, which is source of various growth factors and cytokines proved to be a promising newer stem cell-based strategy for accelerating the wound healing process by promoting cell migration and proliferation, angiogenesis, re-epithelialization, and activating several signaling pathways (such as Wnt/β-catenin, AKT, ERK, and STAT3) [ 169 , 174 ]. Adipose-derived MSCs are also very commonly utilized in wound healing applications due to its high accessibility, minimal invasiveness, and lack of ethical limitations [ 156 , 175 ]. Recently, exosomes that were derived from adipose-derived MSCs have shown accelerated wound healing with a significant increase in the wound closure rate by attenuating the inflammation phase [ 176 , 177 ].…”
Section: Innovative Strategies For Wound Healingmentioning
confidence: 99%
“…In recent years, MSCs-derived exosomes, which is source of various growth factors and cytokines proved to be a promising newer stem cell-based strategy for accelerating the wound healing process by promoting cell migration and proliferation, angiogenesis, re-epithelialization, and activating several signaling pathways (such as Wnt/β-catenin, AKT, ERK, and STAT3) [ 169 , 174 ]. Adipose-derived MSCs are also very commonly utilized in wound healing applications due to its high accessibility, minimal invasiveness, and lack of ethical limitations [ 156 , 175 ]. Recently, exosomes that were derived from adipose-derived MSCs have shown accelerated wound healing with a significant increase in the wound closure rate by attenuating the inflammation phase [ 176 , 177 ].…”
Section: Innovative Strategies For Wound Healingmentioning
confidence: 99%
“…The material was arranged layerby-layer with and without the addition of adipose-derived mesenchymal stem cells. The burn wound healing results of employing cellularised materials were far more effective than acellularised treatments [235]. Meanwhile, it was reported that an autologous homologous adipose tissue, prepared employing 3D bioprinting, successfully accelerated diabetic wound healing with complete wound closure and re-epithelialisation within four weeks [236].…”
Section: Role Of Cell Seedingmentioning
confidence: 99%
“…They demonstrated that tuning the physical and biochemical cues of scaffolds could synergistically direct MSC differentiation into multiple cell lineages, which coordinately promoted sweat gland regeneration. Similarly, Roshangar et al reported a 3D bioprinted gel scaffold from collagen and alginate with adipose-derived stem cells (ADSCs) for burn wound healing ( Roshangar et al, 2021 ). The scaffold increased cell adhesion and proliferation.…”
Section: The Philosophy Of Wound Healing Scaffoldsmentioning
confidence: 99%